Pengaruh Tingkat Pendapatan, Tarif Pajak Dan Sistem Pembayaran Terhadap Kepatuhan Wajib Pajak UMKM: Studi Kasus Kpp Pratama Kota Kediri - Popy Tyara Sari; Fauziyah Fauziyah; Srikalimah Srikalimah (Jurnal Akuntan Publik, 2023)
Taxes are an important element in the country because they have the largest source of income. However, in reality it is still relatively low. This research aims to determine the influence of income levels, tax rates and payment systems on UMKM taxpayer compliance. This research data was obtained from Kediri City Micro Enterprise Data for 2022. Data analysis techniques were carried out using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis analysis to test the influence partially (t test) and simultaneously (F test). The results show that income levels and payment systems have a positive effect on taxpayer compliance with a significance value of 0.000, tax rates have a positive effect on UMKM taxpayer compliance with a significance value of 0.002. KPP Pratama Kediri City must provide the best service and provide counseling so that taxpayers understand the procedures for paying taxes. With the development of technology, it is hoped that taxpayers will be more compliant in paying their obligations. It is hoped that future researchers adding other variables that influence the level of taxpayer compliance, especially for UMKM.